2021
DOI: 10.1002/pld3.329
|View full text |Cite
|
Sign up to set email alerts
|

Impact of nicotine pathway downregulation on polyamine biosynthesis and leaf ripening in tobacco

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…For example, an approximate 90% reduction in nicotine contents has been detected in the leaves of tobacco grafted onto a tomato rootstock (Ruiz et al, 2005 ). In tobacco, alkaloids are synthesized in the roots and subsequently transported to leaves (Nölke et al, 2021 ), and thus grafting tobacco onto an eggplant rootstock effectively removes an important source of synthesized alkaloids. Consequently, the leaves of tobacco growing on an eggplant rootstock had lower alkaloid contents compared with those of the non‐grafted tobacco.…”
Section: Discussionmentioning
confidence: 99%
“…For example, an approximate 90% reduction in nicotine contents has been detected in the leaves of tobacco grafted onto a tomato rootstock (Ruiz et al, 2005 ). In tobacco, alkaloids are synthesized in the roots and subsequently transported to leaves (Nölke et al, 2021 ), and thus grafting tobacco onto an eggplant rootstock effectively removes an important source of synthesized alkaloids. Consequently, the leaves of tobacco growing on an eggplant rootstock had lower alkaloid contents compared with those of the non‐grafted tobacco.…”
Section: Discussionmentioning
confidence: 99%
“…It was revealed that tobacco alkaloids are synthesized from amino acid precursors, among others, via polyamine metabolism due to the activity of the enzyme, putrescine n-methyltransferase (PMT) [46,51]. In addition, a crosstalk between polyamine and alkaloid (nicotine) metabolisms has been established: augmented polyamine levels in low-alkaloid tobacco (Burley 21) were shown to impair leaf ripening [52]. An understanding of polyamine metabolism in tobacco might provide clues to achieve a balance between alkaloid and polyamine metabolism in low-nicotine varieties.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, high-yield tobacco in Bozhou significantly enhanced the urea cycle, leading to increased contents of polyamines and nicotine while altering the isoquinoline alkaloid biosynthesis pathway. However, the breeding objective of tobacco has always been to reduce the levels of nicotine and related alkaloids [48]. Furthermore, a previous study indicated that treatment of tobacco plants with polyamine biosynthesis inhibitors can reduce the polyamine content and ameliorate the phenotype [49].…”
Section: Characteristic Metabolites and Metabolic Pathways Of Differe...mentioning
confidence: 99%